A Porous Tricyclooxacalixarene Cage Based on Tetraphenylethylene1. (18th June 2015) - Zhang, Chun; Wang, Zhen; Tan, Liangxiao; Zhai, Tian‐Long; Wang, Sheng; Tan, Bien; Zheng, Yan‐Song; Yang, Xiang‐Liang; Xu, Hui‐Bi
Abstract A quadrangular prismatic tricyclooxacalixarene cage 1 based on tetraphenylethylene (TPE) was efficiently synthesized by a one‐pot SNAr condensation reaction. As a result of the porous internal structure in the solid state, cage 1 exhibited a good CO2 uptake capacity of 12.5 wt % and a high selectivity for CO2 over N2 adsorption of 80 (273 K, 1 bar) with a BET surface area of 432 m2 g−1. Formation of cage 1 led to the fluorescence of TPE being switched on in solution. The system was employed as a single‐molecule platform to study the mechanism of aggregation‐induced emission (AIE) by examining the restriction of intramolecular rotation (RIR).